No effect of pre-exercise meal on substrate metabolism and time trial performance during intense endurance exercise - Paul, D.; Jacobs, K. A.; Geor, R. J.; Hinchcliff, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
To determine the effect of macronutrient composition of pre-exercise meals on exercise metabolism and performance, 8 trained men exercised for 30 min above lactate threshold (30LT), followed by a 20-km time trial (TT). Approximately 3.5 h before exercise, subjects consumed a carbohydrate meal (C; 3 g carbohydrate/kg), an isoenergetic fat meal (F; 1.3 g fat/kg), or a placebo meal (P; no energy content) on 3 separate occasions in randomized order. Treatments had no effect on carbohydrate oxidation during exercise, but C decreased whole-body fat oxidation during the last 5 min of 30LT and TT, respectively (3.2 ± 1.6 and 4.8 ± 2.1 mmol · kg-1 · min-1, p < .05) when compared to F (13.3 ± 1.6 and 16.5 ± 2.7 mmol · kg-1 · min-1) and P (15.9 ± 2.7 and 17.0 ± 3.2 mmol · kg-1 · min-1). Glucose rate of appearance (Ra) and disappearance (Rd), and muscle glycogen utilization were not significantly different among treatments during exercise. TT performances were similar for C, F, and P (32.7 ± 0.5 vs. 33.1 ± 1.1 and 33.0 ± 0.8 min, p > .05). We conclude that the consumption of a pre-exercise meal has minor effects on fat oxidation during high-intensity exercise, and no effect on carbohydrate oxidation or TT performance.